APARTHEID’S LOST ATTACHMENTS (2): MELANCHOLIC LOSS AND SYMBOLIC IDENTIFICATION - Hook, Derek (PINS-Psychology in Society, 2025)
This paper, the second of two focussed on the libidinal attachments of white children to black domestic workers in narratives contributed to the Apartheid Archive Project (AAP), considers the applicability of the concept of social melancholia in the case of such “inter-racial” attachments. The paper questions both the psychoanalytic accuracy, and the psychic and political legitimacy of such an explanation (that is, the prospect of an “inter-racial” melancholic attachment of white subjects to black care-takers). By contrast to the political notion of ungrievable melancholic losses popularized by Judith Butler’s work, this paper develops a theory of compensatory symbolic identifications. Such a theory explains the apparent refusal of identification which white subjects exhibit towards black caretakers and it throws into perspective an important conceptual distinction regards loss. On the one hand there is the psychotic mechanism of melancholic attachment, which expresses absolute fidelity to a lost object, even to the point of self-destructive suffering. On the other, there is the neurotic mechanism of compensatory identification, in which the original object is jettisoned and a substitution found, such that a broader horizon of symbolic and ideological identification is enabled.